2013
DOI: 10.1158/1541-7786.mcr-12-0665
|View full text |Cite
|
Sign up to set email alerts
|

RASSF1A-Mediated Regulation of AREG via the Hippo Pathway in Hepatocellular Carcinoma

Abstract: Ras association domain family 1 isoform A (RASSF1A) is a tumor suppressor that is methylated in many human cancers, including hepatocellular carcinoma (HCC). RASSF1A has been shown to suppress tumors via activation of the Hippo tumor suppressor pathway, including mammalian STE20-like kinase (MST). Amphiregulin (AREG), a target gene for Yes-associated protein (YAP), is a known oncogenic component of the Hippo pathway; however, the tumor-suppressive effect of RASSF1A on AREG in regard to regulation of the Hippo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…Activated LATS1/2 phosphorylate YAP, which inhibited cell proliferation in mammalian cells 38, 39, 40. In confirmation that WWC2 activates the Hippo pathway in HCC, overexpression of WWC2 in SMMC‐7721 cells (which express low levels of WWC2) increased phosphorylation of both LATS and YAP, which has been previously shown to negatively regulate the Hippo pathway 11, 41, 42. The latter study also revealed HCC cells transfected with the WWC2 overexpression plasmid decreased the mRNA level of Cyr61 and CTGF, both which are the target genes of Hippo pathway.…”
Section: Discussionmentioning
confidence: 55%
“…Activated LATS1/2 phosphorylate YAP, which inhibited cell proliferation in mammalian cells 38, 39, 40. In confirmation that WWC2 activates the Hippo pathway in HCC, overexpression of WWC2 in SMMC‐7721 cells (which express low levels of WWC2) increased phosphorylation of both LATS and YAP, which has been previously shown to negatively regulate the Hippo pathway 11, 41, 42. The latter study also revealed HCC cells transfected with the WWC2 overexpression plasmid decreased the mRNA level of Cyr61 and CTGF, both which are the target genes of Hippo pathway.…”
Section: Discussionmentioning
confidence: 55%
“…Consistently, most research groups observed more than 50% of human liver cancer tumors show elevated nuclear YAP expression [9,51,[54][55][56][57][58][59][60]. Multiple M a n u s c r i p t mechanisms were attributed to the elevated nuclear YAP expression, including gene amplification [40,56], increased Yap mRNA levels [51,55,56] and the dysregulation of the Hippo signaling with reduced expression of MST1 [47], LATS [57] and RASSF1A [59].…”
Section: Role Of Yap In Liver Cancer Demonstrated By Human Studiesmentioning
confidence: 73%
“…Several genes were proposed as YAP downstream targets in driving liver cancer development, including Axl (AXL receptor tyrosine kinase) [61], Survivin [56] and Amphiregulin [59]. Combining human and mouse data together, YAP is a very promising therapeutic target for liver cancer.…”
Section: Role Of Yap In Liver Cancer Demonstrated By Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations